2019
DOI: 10.1111/cen.13910
|View full text |Cite
|
Sign up to set email alerts
|

Poorly differentiated thyroid cancer in the context of the revised 2015 American Thyroid Association Guidelines and the Updated American Joint Committee on Cancer/Tumor‐Node‐Metastasis Staging System (eighth edition)

Abstract: Summary Objective Poorly differentiated thyroid cancer (PDTC) is a rare, but aggressive thyroid cancer (TC) and a main cause of death from non‐anaplastic follicular cell‐derived TC. Assessing the risk of PDTC‐related death and the risk of recurrence is important for clinicians. The recent American Thyroid Association (ATA) 2015 guidelines and the updated 8th edition of the American Joint Committee on Cancer/Tumor‐Node‐Metastasis (AJCC/TNM) staging system should support clinicians in the management approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…The retrospective study was performed at Holycross Cancer Center (HCC), Kielce, a tertiary referral oncologic center in Poland, that provides comprehensive care for patients with TC and includes surgery, endocrinology, nuclear medicine, and radiation oncology departments, with similar characteristic as described in a previous study site [15]. The recruitment procedure resulting in a study group of 46 consecutive PDTC patients who underwent primary surgery between 2000 and 2017 was reported in details previously in the study with other objectives [15]. Subsequently, three PDTC cases were identified among 234 newly diagnosed TCs at HCC in 2018.…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrospective study was performed at Holycross Cancer Center (HCC), Kielce, a tertiary referral oncologic center in Poland, that provides comprehensive care for patients with TC and includes surgery, endocrinology, nuclear medicine, and radiation oncology departments, with similar characteristic as described in a previous study site [15]. The recruitment procedure resulting in a study group of 46 consecutive PDTC patients who underwent primary surgery between 2000 and 2017 was reported in details previously in the study with other objectives [15]. Subsequently, three PDTC cases were identified among 234 newly diagnosed TCs at HCC in 2018.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…The staging of all cases was re-classified according to the 8 th edition of the American Joint Committee on Cancer/Tumor-Node-Metastases (AJCC/TNM) staging system [17]. All details of the management protocols, including indications for postoperative treatment such as radioiodine (RAI) therapy, external beam radiation therapy (EBRT), or subsequent-line therapies [conventional chemotherapy (CHTH) and tyrosine kinase inhibitor (TKI) therapy], and follow-up protocols, were described previously [15]. Death of the patient was considered disease-related when hospital conclusions were unequivocal or a TC death certificate was available.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…Early diagnosis and treatment yield the best outcome and prognosis[ 100 - 102 ]. A study from the United States including 719 patients found that racial, ethical and socioeconomic status seems to influence survival and prognosis.…”
Section: Managementmentioning
confidence: 99%
“…The Walczyk retrospective study of 46 patients with PDTC treated in a single tertiary referral centre from 2000 to 2017 focused on the clinical usefulness of the recent 2015 American Thyroid Association (ATA) guidelines and the updated 8th edition of AJCC staging system in patients with this rare and aggressive endocrine malignancy . This Polish study emphasized a comprehensive approach to management of PDTC including clinical and pathological factors, initial risk stratification, response to therapy, and follow‐up data including re‐evaluation of initial risk estimates.…”
mentioning
confidence: 99%
“…The 8th edition of the AJCC staging system underestimates the mortality due to PDTC, and the clinical course of patients with PDTC is distinctly worse than predicted by the ATA risk stratification criteria. The current study suggests that the PDTC patients need more appropriate guidelines that distinguish PDTC patients from patients with differentiated thyroid cancer (DTC) …”
mentioning
confidence: 99%